X-ray diffraction study of strain-induced crystallization of hydrogenated nitrile-butadiene rubbers: Effect of crosslink density. (10th April 2023) - Femina, Giuseppe; de Ballesteros, Odda Ruiz; Urciuoli, Gaia; van Duin, Martin; Gögelein, Christoph; Tammaro, Daniele; Sotta, Paul; Auriemma, Finizia
Abstract: The structure and the mechanical and thermal properties of a hydrogenated acrylonitrile-butadiene rubber (HNBR) with acrylonitrile content of 44 wt% and residual unsaturation content of 9% are investigated as a function of the crosslink density. The analysis is focused on specimens that have not been subjected to any prior deformation. All samples are amorphous at room temperature and show glass transition temperatures that increase with increasing crosslink density. The values of the Young's modulus of the vulcanized samples are three times higher than that of the non-vulcanized counterpart and tend to increase with increasing the crosslink density. The tensile strength increases with increasing crosslink density, whereas the deformation at break decreases. All samples are amorphous at low deformations and whereas the non-vulcanized and the weakly and medium crosslinked samples undergo strain-induced crystallization (SIC) above a critical value of deformation, the highly crosslinked samples show only faint SIC and rupture at deformations slightly higher than that at SIC onset. It is shown that the deformation at SIC onset for the crosslinked samples tends to increase with increasing the crosslink density. This is in contrast with the prediction of Flory's theory for a homogeneous network. Instead, in agreement with Flory's predictions, the degree of orientation of the amorphous phase, increases with increasing deformation and reaches a plateau at SIC onset, indicating that the onset of crystallization is associated with a relaxation of the amorphous chains connected to the crystalline stems. The remarkable tensile strength of the crystallizing HNBR samples at high deformations is attributed to the strong alignment of the crystals in the stretching direction formed by SIC, causing pronounced strain hardening. Graphical abstract: Image 1 Highlights: Crosslinked hydrogenated butadiene/acrylonitrile rubbers are analyzed. The samples experience strain-induced crystallization (SIC) at high deformations. Orientation of the amorphous phase increases with deformation up to SIC onset. Deformation at incipient SIC tends to increase with increase of crosslink density. SIC rate tends to increase at high crosslink density.